Scythe & Sparrow - Weaver, Brynne (Weaver, Brynne. Ruinous love trilogy, 2025)
"Doctor Fionn Kane is running from a broken heart, one he hopes to mend in small-town Nebraska, far away from his almost-fianč and his derailed surgical career. It's a simpler life: head down, work hard, and absolutely no romantic relationships. He wants none of the circus he left behind in Boston. But then the Silveria Circus finds him. Motorcycle performer Rose Evans has spent a decade on the road with Silveria, and it suits her just fine, especially when she has the urge to indulge in a little murder and mayhem when she's not in the spotlight. But when a kill goes awry and she ends up with a broken leg, she finds herself stuck in Nebraska at the home of the adorably nerdy town doctor. The problem is, not every broken heart can be sewn back together...And the longer you stay in one place, the more likely your ghosts are to catch up." --